2009
DOI: 10.1016/j.cub.2008.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Specific Protein MCD1 Determines the Site of Chloroplast Division in Concert with Bacteria-Derived MinD

Abstract: Chloroplasts evolved from a cyanobacterial endosymbiont, and chloroplast division requires the formation of an FtsZ division ring, which is descended from the cytokinetic machinery of cyanobacteria. As in bacteria, the positioning of the chloroplast FtsZ ring is regulated by the proteins MinD and MinE. However, chloroplast division also involves mechanisms invented by the eukaryotic host cell. Here we show that a plant-specific protein MULTIPLE CHLOROPLAST DIVISION SITE 1 (MCD1) regulates FtsZ ring positioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 42 publications
(94 reference statements)
4
85
0
Order By: Relevance
“…FtsZ, homolog of the tubulin-like bacterial division GTPase, self-assembles into a ring structure at the stromal side of the division site (Vitha et al, 2001;Kuroiwa et al, 2002). The positioning of the FtsZ ring mid-chloroplast is regulated by MinD, MinE, ARC3, and MCD1 (Colletti et al, 2000;Itoh et al, 2001;Shimada et al, 2004;Nakanishi et al, 2009). FtsZ filaments are stabilized by cyanobacteria-descended inner envelope spanning protein ARC6 (Vitha et al, 2003) through interaction with FtsZ .…”
Section: Resultsmentioning
confidence: 99%
“…FtsZ, homolog of the tubulin-like bacterial division GTPase, self-assembles into a ring structure at the stromal side of the division site (Vitha et al, 2001;Kuroiwa et al, 2002). The positioning of the FtsZ ring mid-chloroplast is regulated by MinD, MinE, ARC3, and MCD1 (Colletti et al, 2000;Itoh et al, 2001;Shimada et al, 2004;Nakanishi et al, 2009). FtsZ filaments are stabilized by cyanobacteria-descended inner envelope spanning protein ARC6 (Vitha et al, 2003) through interaction with FtsZ .…”
Section: Resultsmentioning
confidence: 99%
“…But in many aspects, characters of AtMinD and AtMinE are diverged from their homologs in prokaryotes [26,46,47]. Recently, it was shown that a plant-specific protein, MCD1, is required for FtsZ ring positioning [48]. MCD1 recruits MinD to the chloroplast inner envelope by direct interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the origin of chloroplasts, several chloroplast division proteins are homologs of bacterial cell division proteins (Osteryoung and Vierling, 1995;Colletti et al, 2000;Itoh et al, 2001;Maple et al, 2002;Vitha et al, 2003), and models of bacterial cell division have guided studies and understanding of chloroplast division mechanisms in plants (Okazaki et al, 2010;Miyagishima, 2011). During evolution, plants have also acquired new chloroplast division components of eukaryotic origin (Gao et al, 2003;Miyagishima et al, 2006;Nakanishi et al, 2009).…”
Section: Introductionmentioning
confidence: 90%